2009
DOI: 10.1007/s00394-009-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of the marine carotenoids, fucoxanthin and fucoxanthinol on triglyceride absorption in lymph duct-cannulated rats

Abstract: These results show that these two marine carotenoids inhibit lipase activity in the gastrointestinal lumen and suppress triglyceride absorption, and fucoxanthin was converted to fucoxanthinol in the intestine and released into the lymph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 25 publications
1
55
0
Order By: Relevance
“…The volume temporally decreased after the infusion of methyl mercury. Matsumoto et al [31] also observed a reduction of the flow rate of lymph within 1 h after the infusion of organic components. Although the substance differs from the present study, the same phenomenon may occur.…”
Section: Resultsmentioning
confidence: 91%
“…The volume temporally decreased after the infusion of methyl mercury. Matsumoto et al [31] also observed a reduction of the flow rate of lymph within 1 h after the infusion of organic components. Although the substance differs from the present study, the same phenomenon may occur.…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, the concentration of chitosan in the shrimp residue extracts from the present work is probably low due to the characteristics of the extraction procedures applied (SOX and SFE), which were not appropriated for polysaccharide extraction. Still, fucoxanthin, a carotenoid from xanthophyll group and structurally similar to astaxanthin, has been indicated to reduce the obesity by inhibiting the intestinal lipase activity [51], which may also reduce the plasma triglycerides levels. Moore et al [52] studied the influence of oily fish intake on plasma triacylglycerols from overweight men and women and the results indicated that two portions of oily fish, rich in DHA and EPA, per week led to significant reduction in triglycerides levels, compared to consumption of the same portion of white fish that do not presented significant content of these fatty acids.…”
Section: Anti-obesity and Hypolipidemic Effectsmentioning
confidence: 99%
“…Fucoxanthin isolated from edible seaweeds, and its metabolite fucoxanthinol, have been shown to inhibit pancreatic lipase activity in the gastrointestinal lumen and leading to suppressed triacylglycerol absorption in lymph-duct cannulated rats [32]. In addition, fucoxanthin and fucoxanthinol were found to significantly inhibit pancreatic lipase activity, assayed based on inhibition of the hydrolysis of triolein.…”
Section: Marine Algae As a Source Of Anti-pancreatic Lipase Agentsmentioning
confidence: 99%